IMPORTANCE OF PARTS OF SPEECH (Web of Teachers: Inderscience Research, 2025)
The basic building blocks of language, or parts of speech, are examined in this article with an emphasis on their division into conceptual and functional categories. The fundamental linguistic building blocks known as parts of speech influence sentence form and meaning in communication. Nouns, verbs, adjectives, adverbs, and pronouns are examples of hypothetical parts of speech. Each of these words has a significant lexical meaning and enables the presentation of ideas, actions, connections, and descriptions. On the other hand, grammatical functions include linking words, organizing sentences, and establishing relationships between ideas. Examples of these functions include prepositions, conjunctions, articles, and auxiliary verbs. This article examines these categories to demonstrate how conceptual and functional aspects of speech interact in language creation and how their functions and relationships promote coherent and understandable communication.